Accuracy of point-of-care Panbio™ SARS-CoV-2 antigen-detection test in a socioeconomically vulnerable population in Brazil - Gontijo, Carolina Carvalho; Brito, Raíssa Nogueira de; Teixeira, Ana Izabel Passarella; Romero, Gustavo Adolfo Sierra; Pedrette, Priscilla; Ramalho, Walter Massa; Noronha, Elza; Haddad, Rodrigo; Araújo, Wildo Navegantes de (Frontiers in Tropical Diseases, 2022)
Background Development and validation of point-of-care (POC) diagnostic tests with high accuracy is critical for underrepresented populations, allowing for wider access to diagnosis. Here, we evaluate the performance of the Panbio™ antigen-rapid test device (Ag-RTD) for SARS-CoV-2, our index test, having RT-qPCR as the reference standard. Methods This phase III validation study was conducted concomitantly with a primary health care center routine tending to a low-income Brazilian population. Eligibility criteria were residing at Cidade Estrutural and presenting flu-like/respiratory symptoms for 3-10 days. Results Among the 505 participants, 45.15% (228/505) tested positive for RT-qPCR and 54.85% (277/505) for the Ag-RTD. Overall sensitivity was 76.32% (CI95% 70.39-81.37) and specificity was 98.92% (96.02-99.82). Conclusions Our results show that the Panbio™ Ag-RTD does not meet the minimum performance requirements established by the World Health Organization (≥ 80% sensitivity and ≥ 97% specificity compared to a reference test in suspected COVID-19 cases). Thus, we do not recommend the implementation of Panbio™Ag-RTD as a single diagnostic tool in underrepresented and disadvantaged populations. Finally, we discuss a possible setting for the use of Panbio™Ag-RTD under combined sensitivity.